2016
DOI: 10.7150/jca.15644
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Impact of Lymph Node Metastases in Advanced Ovarian Cancer: Implications for Surgical Treatment

Abstract: Background: This study aimed to clarify the impact of node involvement (affected to resected nodes) in optimally cytoreduced (residual tumour ≤1cm) stage IIIC/IV ovarian cancer.Methods: 108 consecutive patients with primary stage IIIC/IV ovarian cancer underwent stage-related surgery and got adjuvant platinum-based chemotherapy. Median follow-up: 53.5 months. All patients got systematic para-aortic and pelvic lymphadenectomy. Clinical parameters were retrospectively evaluated. Patients were stratified into 3 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 28 publications
0
22
0
1
Order By: Relevance
“…Fournier et al [14] presented similar observations, but the ratio of metastases in primary surgery was 50%. In other studies, metastases to retroperitoneal lymph nodes in early ovarian cancer were found in 13-25% [4,15], while in advanced stage were observed in 45-75% cases [4,7,16,17]. Elective pelvic and aortocaval lymphadenectomy in patients with clinical stage I and II results in final diagnosis of stage III in 20% [4].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Fournier et al [14] presented similar observations, but the ratio of metastases in primary surgery was 50%. In other studies, metastases to retroperitoneal lymph nodes in early ovarian cancer were found in 13-25% [4,15], while in advanced stage were observed in 45-75% cases [4,7,16,17]. Elective pelvic and aortocaval lymphadenectomy in patients with clinical stage I and II results in final diagnosis of stage III in 20% [4].…”
Section: Discussionmentioning
confidence: 80%
“…In our study, we analysed only serous tumors regarding it was the histologic type associated with the most common pelvic and para-aortic lymph nodes involvement. Although Roger et al [18] found similar frequency for lymph nodes involvement in different histological types of epithelial ovarian cancer, other studies presented higher rate of lymph nodes metastases in serous tumor [8,9,16,19,20]. Zhou et al showed higher risk (OR 2.728, 95% CI 1.072-6.945, p = 0.035) for nodal involvement in serous ovarian cancer [8].…”
Section: Discussionmentioning
confidence: 93%
“…The prognostic relevance of lymph node metastases in primary ovarian cancer is unclear, although seen as an important prognostic factor for advanced-stage ovarian cancer, there is contradictory data on survival after systematic lymphadenectomy versus bulky node resection [19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial Ovarian cancer (EOC) accounts for over 4000 deaths in the UK every year [1]. Lymph nodes metastases are very common in EOC-patients and also associated with a more dismal overall prognosis [2-3]. Total macroscopic tumour clearance, is one of the most important prognostic factors for survival post-surgery in EOC, including also the removal of bulky lymph nodes [3-4].…”
Section: Introductionmentioning
confidence: 99%
“…Lymph nodes metastases are very common in EOC-patients and also associated with a more dismal overall prognosis [2-3]. Total macroscopic tumour clearance, is one of the most important prognostic factors for survival post-surgery in EOC, including also the removal of bulky lymph nodes [3-4]. There is no therapeutic value in the systematic removal of clinically normal appearing LN in the advanced disease setting, as shown in prospective randomised trials [5].…”
Section: Introductionmentioning
confidence: 99%